LIFE AND WORK OF THE UZBEK POET MUHAMMAD YUSUF (American Journal of Pedagogical and Educational Research, 2023)
This article provides information about the work of the famous poet of the Uzbek people, Muhammad Yusuf, and the stages of the creation of his poems.